Assessment and prediction of voltage sag in transmission system in northern area of Thailand - P. Saninta (2018)
This paper presents a method for stochastic prediction of voltage sags caused by a fault in the transmission system of Electricity Generating Authority of Thailand (EGAT). The magnitude of voltage sags calculated and the duration of voltage sag is analyzed by the fault clearing times of the transmission system using operating time of relay protection and circuit breaker. The probability of voltage sags with affected to electrical is also analyzed. The area of vulnerability must be determined based on Information Technology Industry Council (ITIC) curve. The mitigation method of voltage sag is considered at both side utility side and customer side. ©2008 IEEE.